2006
DOI: 10.1007/s11136-005-3212-1
|View full text |Cite
|
Sign up to set email alerts
|

ISSQoL: A New Questionnaire for Evaluating the Quality of Life of People Living with HIV in the HAART Era*

Abstract: The data reported in the present paper provide preliminary evidence of the reliability and validity of the ISSQoL questionnaire for the measurement of HRQoL in HIV-infected people. The direct involvement of HIV-positive people in all the phases of the project was a key aspect of our work.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0
7

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 25 publications
1
17
0
7
Order By: Relevance
“…In our experience, self-administered questionnaires are suitable to assess psychiatric and other adverse events among chronic patients on therapy, as reported in literature in other medical settings. [35][36] The impact of Peg-IFN and ribavirin on the cytokine patterns is not completely clear. [16][17][18] In the literature some authors have suggested that some cytokines (eg.…”
Section: Discussionmentioning
confidence: 99%
“…In our experience, self-administered questionnaires are suitable to assess psychiatric and other adverse events among chronic patients on therapy, as reported in literature in other medical settings. [35][36] The impact of Peg-IFN and ribavirin on the cytokine patterns is not completely clear. [16][17][18] In the literature some authors have suggested that some cytokines (eg.…”
Section: Discussionmentioning
confidence: 99%
“…1 Since the advent of HAART, the survival rate for HIV patients has increased and the assessment of HRQoL has become a priority for patients, physicians and researchers. 2 The ISSQoL is comprised of two sections, which may be jointly or separately used: the Core Evaluation Form and the Additional Important Areas Form.…”
Section: Introductionmentioning
confidence: 99%
“…As it regards content validity 5,7,8 (ie, a type of validity which examines the extent to which a specific field of interest has been comprehensively sampled by the items, or questions included in the instrument), the ISSQoL-CEF items and domains can be reasonably considered as representative of the HRQoL HIV-infected people, since they were generated based on a comprehensive literature review of HRQoL facets as well as on a content analysis of existing specific questionnaires for HIV-infected people. 1 As it concerns face validity 5,7,8 (ie, a type of validity which considers how a questionnaire measure appears to its end-users and respondents), we have refined the item wording and improved the questionnaire's perceived utility by discussing preliminary CEF versions with HIV-infected people in repeated focus groups. 1 Along with the appraisal of content and face validity, the psychometric theory 3,5,7,8 calls, however, for a more compelling assessment of construct validity as a mandatory step prior to licensing a questionnaire as a "ready for use" instrument in research and clinical settings.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Apesar da aids ser incurável, os avanços científicos referentes ao diagnóstico e sobretudo ao tratamento medicamentoso, com a utilização da terapia antiretroviral, proporcionaram redução da morbimortalidade e significativo aumento na sobrevida dos indivíduos com o HIV/aids, uma vez que esta deixou de ser considerada como doença incurável, fatal e irreversível, tornando-se uma condição crôni-ca potencialmente controlável (1) .…”
Section: Introductionunclassified